TikTok Shop: How Social Commerce Shapes Purchase Decisions - Winoto, Agung; Supu, Mahfud; Nunu, Arson; Armawati, Armawati (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to analyze the influence of social commerce elements, such as social interaction, transaction convenience, creative content, user-generated content (UGC), and live shopping, on consumer purchase decisions on the TikTok Shop platform in Indonesia. Using a quantitative approach with an explanatory research design, this study involved respondents who had made purchases within the last six months. Regression analysis indicates that four main variables, like social interaction (p = 0.014), transaction convenience (p = 0.009), creative content (p = 0.012), and UGC (p = 0.012) are significantly affect purchase decisions. Meanwhile, live shopping does not show a significant influence (p = 0.115), suggesting that direct synchronous interaction on TikTok Shop is not sufficient to drive purchase conversion without strong support from information quality and credibility.